Childhood Granulomatous Periorificial Dermatitis with a Good Response to Oral Metronidazole. Issue 5 (26th February 2013) - Rodriguez‐Caruncho, Clara; Bielsa, Isabel; Fernandez‐Figueras, M Teresa; Ferrándiz, Carlos
Abstract Childhood granulomatous periorificial dermatitis (CGPD) is a condition included in the spectrum of rosacea and perioral dermatitis that affects prepubescent children. It is characterized by papular eruptions located around the mouth, nose, and eyes that histopathologically show a granulomatous pattern. We report a 9‐year‐old girl with CGPD who required treatment with an oral antibiotic. Oral metronidazole was administered because of its known efficacy in adult rosacea and its safety in children. The patient responded well to this therapy, showing resolution of the lesions.